Insulating and fire‐resistant performance of slag and brick powder based one‐part alkali‐activated lightweight mortars - Koksal, Fuat; Bayraktar, Oguzhan Yavuz; Bodur, Burak; Benli, Ahmet; Kaplan, Gokhan (Wiley, 2022)
AbstractWaste brick powder (WBP) has enough pozzolanic characteristics to be employed as a supplemental cementing material in Portland cement‐based concrete or as a precursor in the manufacture of alkali activated materials. This study was aimed to study the strength, thermal, microstructural and durability properties of ground blast furnace slag (GBFS) and WBP based one‐part alkali‐activated lightweight mortars (AAMs) produced with expanded vermiculite. One‐part AAM mixtures were produced by using GBFS and WBP as binary precursors. Sodium metasilicate powder was used as the alkali activator. Two curing regimes namely heat curing at 75°C for 24 h and air curing at ambient conditions were adopted. GBFS was used as main binder and WBP was added at the rates of 0%, 10%, 25%, and 50% instead of GBFS. Four different mixtures were prepared by replacing GBFS at the rates of 0%, 10%, 25%, and 50% with WBP for each curing regime (totally eight mixtures). Expanded vermiculite powder were used as lightweight aggregates in all mixtures. The effects of WBP on AAM mixtures properties, including flowability, compressive strength, flexural strength, dry bulk density, thermal conductivity, porosity, and water absorption were studied. The effects of WBP and curing regime on drying shrinkage, sorptivity were also investigated. High temperature performance of the produced mixtures were determined. Results showed that air‐cured WBP incorporated AAM mixtures exhibited better compressive strength, flexural strength, shrinkage, and sorptivity performance than the heat‐cured WBP incorporated AAM mixtures. The air‐cured AAM mixtures containing 25% WBP achieved the best results of 5.69 and 1.43 MPa for compressive strength and flexural strength at test age of 28 days. The heat‐cured 50% WBP incorporated AAM mixture showed the best high temperature resistance and the lowest thermal conductivity.
Keywords: 6. Clean water; 12. Responsible consumption